CITRA PEREMPUAN DALAM KABA SI GADIH RANTI KARYA SYAMSUDDIN SUTAN RADJO ENDAH - Fani, Sevta; Nurizzati, Nurizzati; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2018)
This study aims to describe the female image in Kaba Si Gadih Ranti by Syamsuddin Sutan Radjo Endah, in terms of three aspects: (1) the image of women as individuals, (2) the image of women as family members and (3) the image of women as community members. An image is a person's personal image that can be seen from the actions, speeches, associations, dresses and patterns of thinking that develop in every problem faced. While kaba is one of the classic works of Minangkabau society in the form of prose which contains the reality of Minangkabau life that is delivered orally, and serves as entertainment, as advice, as moral and cultural education. This type of research is qualitative research with descriptive methods. Based on the analysis of its contents, which describes the facts found in the object of research based on content. Analyzing data, namely (1) describing data concerning the image of women in Kaba Si Gadih Ranti by Syamsuddin Sutan Radjo Endah; (2) analyzing data based on the classification found; (3) interpret data based on classifications found; (4) draw conclusions and write reports from the results of the description carried out. The results of this study conclude that the image of women in Kaba Si Gadih Ranti is: (1) the image of women as individuals who include beauty, gentle, humble, (2) the image of women as family members which includes the role of wife, mother and children , family members, and (3) the image of women as members of the community that include environmental concerns or others and relationships to the environment or others.Keywords: Kaba, Image of women, Kaba Si Gadih Ranti